The Research Imagination During Covid-19: Rethinking Norms of Group Size and Authorship in Anthropological and Anthropology-adjacent Collaborations - Long, Nicholas; Hunter, Amanda; Appleton, Nayantara Sheoran; Davies, Sharyn; Deckert, Antje; Sterling, Rogena; Tunufa'I, Laumua; Aikman, Pounamu Jade; Fehoko, Edmond; Holroyd, Eleanor; Jivray, Naseem; Laws, Megan; et al. (Taylor and Francis Group, 2023)
This article explores some of the ways in which the COVID-19 pandemic has served as a collective critical event for anthropologists and other social scientists, examining how it has promoted new configurations of the research imagination. We draw on our own experiences of participating in a team of 17 researchers, hailing from anthropology and anthropology-adjacent disciplines, to research social life in Aotearoa/New Zealand during the pandemic, examining how our own research imaginations were transformed during, and via, the process of our collaboration. When our project first began, many of us had doubts reflective of norms, prejudices and anxieties that are common in our disciplines: that the group would be too large to function effectively, or that it would be impossible to develop an approach to authorship that would allow everyone to feel their contributions had been adequately recognised. In practice, the large group size was a key strength in allowing our group to work effectively. Difficulties with authorship did not arise from within the group but from disconnects between our preferred ways of working and the ways authorship was imagined within various professional and publishing bodies. We conclude that large-scale collaborations have many points in their favour, and that the research imaginations of funders, journals, universities and professional associations should be broadened to ensure that they are encouraged, supported and adequately rewarded.
Keywords: 1601 Anthropology; 1699 Other Studies in Human Society; Anthropology; 4401 Anthropology; academia; Aotearoa/New Zealand; collaborative methods; pandemic; research teams